Oral health and microbiota status in professional rugby players: A case-control study. (December 2018) - Minty, Matthieu; Canceill, Thibault; Lê, Sylvie; Dubois, Pauline; Amestoy, Oihana; Loubieres, Pascale; Christensen, Jeffrey E.; Champion, Camille; Azalbert, Vincent; Grasset, Estelle; Hardy, Sara; Loubes, Jean-Michel; et al.
Abstract: Objective: Elite athletes are prone to develop oral diseases, which could increase the risk for injuries. The aim of this study was to evaluate the oral health and the composition of oral microbiota of elite rugby players compared to the general population. Methods: We set up a case-control study by screening 24 professional rugby players (PRG) and 22 control patients (CG) for dental and gingival examinations and performed a taxonomic analysis and a predicted functional analysis of oral microbiota. Results: The Decay, Missing and Filled (DMF) teeth index (5.54  ± 6.18 versus 2.14 ± 3.01; p =  0.01) and the frequency of gingivitis (58, 33% versus 13.63%) were significantly increased in PRG compared to CG. PRG were characterized by a dysbiotic oral microbiota (Shannon Index: 3.32 ± 0.62 in PRG versus 3.79 ± 0.68 in CG; p = 0.03) with an increase of Streptococcus (58.43 ± 16.84 versus 42.60 ± 17.45; p = 0.005 ), the main genus implicated in caries. Predicted metagenomics of oral microbiota in rugby players was suggestive of a cariogenic metagenome favourable to the development of caries. Conclusions: Our study shows that the oral health of PRG was poorer than the general population. PRG are characterized by a dysbiotic oral microbiota with an increase of the relative abundance of Streptococcus genus, positively correlated to the weight and negatively correlated to the diversity of oral microbiota. Clinical significance: Dental screening should be included in the medical follow-up of professional rugby players as a part of their health management. New strategies such as using probiotics like Lactobacillus could help to control the dysbiosis of oral microbiota.